You feel it just below the ribs : a novel - Cranor, Jeffrey, 1975-; Matthewson, Janina (HarperPerennial, 2021)
"A haunting, provocative novel, You Feel It Just Below the Ribs is a fictional autobiography in an alternate twentieth century that chronicles one woman's unusual life, including the price she pays to survive and the cost her choices hold for the society she is trying to save. Born at the end of the old world, Miriam grows up during The Great Reckoning, a sprawling, decades-long war that nearly decimates humanity and strips her of friends and family. Devastated by grief and loneliness, she emotionally exiles herself, avoiding relationships or allegiances, and throws herself into her work -- disengagement that serves her when the war finally ends, and The New Society arises. To ensure a lasting peace, The New Society forbids anything that may cause tribal loyalties, including traditional families. Suddenly, everyone must live as Miriam has chosen to -- disconnected and unattached. A researcher at heart, Miriam becomes involved in implementing this detachment process. She does not know it is the beginning of a darkly sinister program that will transform this new world and the lives of everyone in it. Eventually, the harmful effects of her research become too much for Miriam, and she devises a secret plan to destroy the system from within, endangering her own life. But is her "confession" honest -- or is it a fabrication riddled with lies meant to conceal the truth? A jarring and uncanny tale of loss, trauma, and the power of human connection and deception, You Feel It Just Below the Ribs is a portrait of a disturbing alternate world eerily within reach, and an examination of the difficult choices we must make to survive in it." --